Il diritto della Chiesa tra Oriente e Occidente. A proposito di un volume di Vittorio Parlato - Varnier, Giovanni Battista (Studi Urbinati, A - Scienze giuridiche, politiche ed economiche, 2013)
A record of the activities of the “Istituto superiore di Scienze religiose”, founded by Italo Mancini, as well as a record of the research activities of its first few years. A recognition of the scholarly activities of Vittorio Parlato, a colleague and friend, who produced research guidelines which shall be remembered – namely the individualisation and protection of the rights of citizens- believers, the meeting with Orthodoxy and the prevalent attention to the juridical-confessional reality of Eastern Christianity. The most original and well-established of these themes regards the law of the Churches and of the religious confessions of Eastern Christianity, as well as the theme of the links between Catholicism and Orthodoxy.